A case of clubbed down syndrome in broilers. Issue 2 (4th March 2021) - Van Limbergen, Tommy; Ronsmans, Stefan; Maes, Dominiek; Van Erum, Johan; Van Ginderachter, Jan; Verlinden, Marc; Boel, Filip; Garmyn, An; Dewulf, Jeroen; Ducatelle, Richard
ABSTRACT: This study presents a case of clubbed down syndrome in conventional broilers. During the first week of life, severe growth retardation was observed in approximately 25% of the flock. The growth-retarded chicks weighed only 45 g and showed a typical feather disorder which was most apparent on their abdomen and was defined in literature as typical for clubbed down syndrome. Necropsies, histology, biochemical analysis of blood and liver samples, serology and different PCR tests were performed in broilers to assess the aetiology of the clinical signs that were present in the affected broiler farm. Because of the suspicion of a possible link with the broiler-breeder farms, different investigations including serology, PCR and feed analysis were also performed on these farms. The results suggest that an accidentally excessive amount of calcium and iron in the feed of broiler-breeders, 3 weeks prior to first clinical signs in broilers, led to the development of clubbed down in the offspring, because of a relative Zn-deficiency in broiler-breeders and an absolute Zn-deficiency in the hatching eggs that were produced during this period. This appeared to be a reversible process as no clinical signs were observed in younger offspring of these broiler-breeders after they had consumed more of the new batch of feed. A potential involvement of Astrovirus could not be completely ruled out. This study demonstrates the importance of correct mineral concentrations in broiler-breeder feed and the impact it can have on the development of the offspring.